Antimicrobial resistance of Staphylococcus aureus isolated from bovine mastitis: Systematic review and meta-analysis - Molineri, Ana Ines; Camussone, Cecilia; Zbrun, María Virginia; Suarez Archilla, Guillermo; Cristiani, Mariana; Neder, Veronica Elizabeth; Calvinho, Luis Fernando; Signorini Porchiett, Marcelo Lisandro (Elsevier, 2021)
Staphylococcus aureus, one of the main contagious mastitis pathogens worldwide, is characterized for causing chronic intramammary infections that respond poorly to antimicrobial therapy, disseminating within the herd leading to high economic losses. The aim of this study was to determine the prevalence of phenotypic resistance to antimicrobial agents among S. aureus collected worldwide in the context of bovine intramammary infections between the years 1969−2020. A systematic review was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). One hundred and fifty-five articles were eligible for quantitative review. Most of studies included in this meta-analysis were from Europe (88), followed by Asia (56), Latin America (39), Africa (32), North America (26), and Oceania (8). The highest overall prevalence of resistant S. aureus was against penicillin (pestimate 0.451, CI95 % 0.415−0.487), followed by clindamycin, erythromycin, and gentamycin (p-estimate = 0.149, 0.085, and 0.069, respectively). Ceftiofur and cephalotin presented the lowest overall prevalence of antimicrobial resistance (AMR, p-estimate = 0.020 and 0.015, respectively). The AMR to almost all the antimicrobials evaluated presented an increasing pattern over time, more apparent from 2009 onwards. The antimicrobials with a higher increase in their AMR prevalence over time were clindamycin, gentamycin, and oxacillin. Africa, Asia and Latin America were the continents with higher AMR to most compounds included in this study. No differences in AMR were detected regarding the clinical origin of the isolates (subclinical vs clinical mastitis) for almost all antibiotics evaluated. Differences in the method for testing AMR (disc diffusion method vs minimum inhibitory concentration) and type of study design for monitoring AMR were detected underscoring the importance of these variables as critical factors to enable comparisons for evaluating emergence of AMR.